ADULT-ONSET STILL'S DISEASE: DIAGNOSIS AND TREATMENT - Rimma Mikhailovna Balabanova; O N Egorova (Современная ревматология, 2009)
The paper describes adult-onset Still's disease (AOSD), a rare multisystemic disease of unknown etiology that is referred to as seronegative rheumatoid arthritis. It presents the major manifestations of AOSD: long-term fever, arthritis or persistent arthralgias, maculopapular eruption, seronegativity for rheumatoid factor, neutrophilic leukocytosis, and disease onset after 16 years of age, as well as additional signs: lymphadenopathy, hepatosplenomegaly, polyserositis, nasopharyngeal infection. It is noted that particular difficulties in the diagnosis of AOSD emerge when it is complicated by the hematophagocytic syndrome (HPS). The distinctive features of AOSD are the development of cutaneous and articular symptoms in practically 80% of patients and their absence in HPS. It is stated that of greater value in the diagnosis of HPS is examination of aspirate of the bone marrow than its biopsy. Most patients develop refractoriness to glucocorticoids and essential anti-inflammatory drugs. The positive results of using anakinra, rituximab, and tocilizumab are promising.